Konsep Pendidikan Karakter dalam Kitab Ta`Limul Muta`Aallim Karya Imam Az-Zarnuji dan Relevansinya Terhadap Kurikulum Merdeka Belajar - Nurullah Nurullah; Asrorudin Asrorudin (Khulasah : Islamic Studies Journal, 2022)
Education is a knowledge, skills, and attitudes that must be possessed by every student, and especially Character Education that must also be embedded in the souls of students, many students do not know their character and violate good ethics. The reality that is currently happening is really sad, "The moral degradation of the younger generation" seems to be a series of sentences that are appropriate to describe the condition or moral behavior of the millennial young generation in the current era. Many Indonesian youths behave abnormally, such as fighting between friends, lack of respect for their parents, even murder, theft, and sex crimes. This research is a qualitative research in the nature of library research (library research). In order to obtain valid research results, it is necessary to select sources, both primary and secondary data sources. The primary data source of this research is the book "Ta`limul Muta``alim" by Imam Az-Zarnuji. While the secondary data source is the Independent Study Ministry of Education and Culture independent study curriculum documents relating to relevant character education. The concept of character education in the book Ta`limul Mutaàllim by Imam Az-Zarnuji is the intention to seek knowledge, choose knowledge, teachers and friends, echo knowledge and Ulama, sincerity, continuity, and enthusiasm, learning methods, tawakkal, and wara` while studying. The relevance of Character Education in the book Ta`limul Muta`allim by Imam Az-Zarnuji with the Independent Study Curriculum, namely accepting (choosing knowledge, teachers and friends), carrying out (sincerity, continuity, and enthusiasm), appreciating (extending knowledge and scholars), living ( learning methods), and practice (tawakkal and wara` when studying).